2011
DOI: 10.1007/s12237-011-9391-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Common Reed, Phragmites australis, in the Mississippi River Delta Marshes: Evidence for Multiple Introductions

Abstract: Multiple introductions are believed to play an important role in increasing genetic diversity and adaptability of invasive species, but there are few well-documented examples. The common reed, Phragmites australis, has dramatically increased in tidal wetlands throughout the USA in the past century due primarily to the introduction of a Eurasian lineage. In the Mississippi River "Balize" delta, P. australis is the dominant vegetation where monotypic stands of an introduced form blanket the outer marshes. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
117
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(121 citation statements)
references
References 54 publications
2
117
0
Order By: Relevance
“…Historically, Phragmites was only a minor component of tidal marsh vegetation assemblages and was confined to higher elevations at the upland boarders of marshes and areas along creek banks (Niering et al 1977;Warren et al 2001). However, recent expansion of Phragmites into more diverse habitats has been occurring along the U.S. Atlantic and Gulf coasts (Chambers et al 1999;Peterson and Partyka 2006;Hauber et al 2011). Reasons for the Phragmites expansion vary by location but can include tidal restrictions, habitat modification, disturbance, and invasion by a more competitive European population (Chambers et al 1999;Burdick et al 2001;Howard et al 2008;Hauber et al 2011).…”
Section: Dominant Forcing Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Historically, Phragmites was only a minor component of tidal marsh vegetation assemblages and was confined to higher elevations at the upland boarders of marshes and areas along creek banks (Niering et al 1977;Warren et al 2001). However, recent expansion of Phragmites into more diverse habitats has been occurring along the U.S. Atlantic and Gulf coasts (Chambers et al 1999;Peterson and Partyka 2006;Hauber et al 2011). Reasons for the Phragmites expansion vary by location but can include tidal restrictions, habitat modification, disturbance, and invasion by a more competitive European population (Chambers et al 1999;Burdick et al 2001;Howard et al 2008;Hauber et al 2011).…”
Section: Dominant Forcing Functionsmentioning
confidence: 99%
“…However, recent expansion of Phragmites into more diverse habitats has been occurring along the U.S. Atlantic and Gulf coasts (Chambers et al 1999;Peterson and Partyka 2006;Hauber et al 2011). Reasons for the Phragmites expansion vary by location but can include tidal restrictions, habitat modification, disturbance, and invasion by a more competitive European population (Chambers et al 1999;Burdick et al 2001;Howard et al 2008;Hauber et al 2011). For example, in coastal Mississippi Peterson and Partyka (2006) found that Phragmites was widespread along creek banks in up-estuary/low salinity environments where there was little anthropogenic disturbance, but Phragmites also occurred in high elevation/high salinity areas that were heavily modified by man.…”
Section: Dominant Forcing Functionsmentioning
confidence: 99%
See 3 more Smart Citations